Integrated bioprocess engineering - Posten, Clemens (De Gruyter Textbook, 2018)
Bioprocess engineering employs microorganisms to produce biological products for medical and industrial applications. The book covers engineering tasks around the cultivation process in bioreactors including topics like media design, feeding strategies, or cell harvesting. All aspects are described from conceptual considerations to technical realization. It gives insight to students of technical biology, bioengineering, and biotechnology by detailed explanations, drawings, formulas, and example processes. In Bioprocess Engineering upstream, bioreaction, and downstream stages are closely linked to each other. From a biological point of view photo-biotechnology is in the centre of interest as well as processes, where the particulate properties play an important role. The main technical means are fermentation under highly controlled conditions, mathematical modelling of bioprocesses including measurement of intracellular compounds, as well as mechanical separation methods arising from downstream processing.